Hubungan antara Umur dan Jenis Kelamin dengan Penerimaan Vaksinasi Covid-19 di Wilayah Kerja Puskesmas Kawangkoan Barat - Deysi Ivoneke Juliske Pantow; Suryadi Tatura; Jeini Ester Nelwan (STIKes Payung Negeri Pekanbaru, 2022)
Introduction: The one way to prevent the spread of COVID-19 is vaccination. The provision of the Covid-19 vaccine in Indonesia has now reached 3 stages, namely primary vaccinations 1 and 2 and added a 3rd or booster vaccination. However, in some areas the coverage of stage 2 vaccination is still <70%. Acceptance of the Covid-19 vaccination is influenced by multifactors such as age and gender. The purpose of this study was to analyze the correlation between age and gender with the acceptance of Covid-19 vaccination in the working area of ​​the Kawangkoan Barat Public Health Center. Method: This is a correlational research. This research was conducted in the working area of ​​the Kawangkoan Barat Public Health Center in February-July 2022. The research respondents were 400 people aged 18 years and over. The variables in this study were age, gender and vaccination acceptance. The instrument used is a filling sheet. Data analysis was carried out bivariately using the chi-square test. Results: The results showed that the age was significantly correlation with vaccination acceptance. In addition, the prevalence ratio (PR) value of 1.504 was obtained, which means that respondents aged 18-59 years were at risk of 1.504 times receiving incomplete vaccinations. Furthermore, it was also found that gender was not significantly correlation with vaccination acceptance. Conclusion: It can be concluded that the age is a factor correlated to Covid-19 vaccination acceptance.